IL-10 Enhances Human Natural Killer Cell Effector Functions via Metabolic Reprogramming Regulated by mTORC1 Signaling - Wang, Zixi; Guan, Di; Huo, Jianxin; Biswas, Subhra K.; Huang, Yuhan; Yang, Yuansheng; Xu, Shengli; Lam, Kong-Peng (Frontiers in Immunology, 2021)
Cell metabolism plays a pivotal role in regulating the effector functions of immune cells. Stimulatory cytokines, such as interleukin (IL)-2 or IL-12 and IL-15, activate glycolysis and oxidative phosphorylation in natural killer (NK) cells to support their enhanced effector functions. IL-10, a pleiotropic cytokine, is known to suppress macrophages activation but stimulate NK cells. However, it remains unclear if IL-10 has an effect on the metabolism of human NK cells and if so, what metabolic mechanisms are affected, and how these metabolic changes are regulated and contribute to the effector functions of NK cells. In this study, we demonstrate that IL-10 upregulates both glycolysis and oxidative phosphorylation in human NK cells, and these metabolic changes are crucial for enhanced effector functions of NK cells. Mechanistically, we unravel that IL-10 activates the mammalian target of rapamycin complex 1 (mTORC1) to regulate metabolic reprogramming in human NK cells.